2012
DOI: 10.1177/0741088312466532
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Information

Abstract: The case study reported here explores the processes involved in producing a written synthesis of three history texts and their possible relation to the characteristics of the texts produced and the degree of comprehension achieved following the task. The processes carried out by 10 final-year compulsory education students (15 and 16 years old) to produce their syntheses, including the integrations they verbalized while performing the task, were examined in detail with a double-analysis system. The results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 29 publications
2
32
0
1
Order By: Relevance
“…However, many students find writing synthesis texts challenging. This is not surprising given the cognitively demanding nature of this task (Martínez, Mateos, Martín, & Rijlaarsdam, 2015;Mateos, Martín, Villalón, & Luna, 2008;Solé, Miras, Castells, Espino, & Minguela, 2013).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…However, many students find writing synthesis texts challenging. This is not surprising given the cognitively demanding nature of this task (Martínez, Mateos, Martín, & Rijlaarsdam, 2015;Mateos, Martín, Villalón, & Luna, 2008;Solé, Miras, Castells, Espino, & Minguela, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…In the latter case, these reading activities play an intermediary role during the writing activity and act as a mediator. Martínez et al (2015), Solé (2009), andSolé et al (2013) found a positive correlation between the quality of a synthesis text and the amount of recursion and mediation during the process in audio-video recordings of students' synthesis processes. These findings seem in accordance with the very nature of the synthesis task, which involves sub-processes such as comparing and contrasting the information from the different sources, linking the sources to one another and integrating the information in a new independent text.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Az ilyen jellegű szövegalkotás általában kevésbé törekszik a témakör, terület meglévő tudásának szintetizálására, mint inkább forrásszöve-gek stratégiai integrálására, mintavételezésére és új kontextusba helyezésére. A szakemberek célja tehát gyakran nem a forrásokban található információk összegzése, szintetizá-lása (Solé, Miras, Castells, Espino, & Minguela, 2013), hanem az ott található információk elemzése, a legértékesebb gondolatok kiválogatása és összegyűjtése innovatív megoldá-sok megfogalmazása érdekében (Leijten et al, 2013) barkácsolt tartalom (bricolage) (Turkle, 1997), egyveleg (pastiche) (Slattery, 2007) létrehozása által. A dokumentum ismételt felhasználása és adaptációja tehát a szakmai kommunikáció gyakorlatában folyamatosan jelen van (Swarts, 2010).…”
Section: A Forrásalapú íRás Alkalmazási Területei éS Fejlesztési Leheunclassified